Creative reading: using books in the vernacular context of Anglo-Norman England - Sargan, J (2018)
This thesis responds to a lack of information regarding reading practice in literature in early Middle English. Here, reading is often used as a metaphorical or symbolic act—representing piety, devotional practice, or intellectualism—but how reading took place, how users engaged with books, is rarely figured. Other seams of evidence are therefore needed to access the reading process. The corpus of manuscripts on which I focus consists of thirty-three multilingual books containing English, Latin, and French produced in England between 1066 and c. 1300. Using this corpus, and inspired by the work of Leah Price, Juliet Fleming, Kathryn Rudy, and others, I seek to test the boundaries of what has previously been considered permissible evidence for reading, thereby adjusting and expanding current conceptions of the range of activities and practices high medieval book use entailed. The thesis begins with a case study of some important readers: scribes. In chapter one, using the seven surviving copies of Poema Morale as a corpus I read against current critical considerations of variance in manuscript transmission as a sign of ‘scribal authorship’ in order to establish practices of scribal reading. Chapters two and three go on to demonstrate how these ‘scribal readers’ prefigured a work’s use as they copied, particularly when they chose to introduce or exclude textual apparatus in the form of titles, capitals, or paraph marks. The final part of the thesis examines the retrospective evidence of use left by readers who marked and altered their books to determine the extent to which readers conformed to the practices imagined by manuscript producers. As a whole, then, the thesis showcases the variegated nature of reading practice—from critical analysis to nugatory scanning—and the alternative uses for books in English in this period. It shows that vernacular reading was a work of ‘embodied intellectual labour’ that benefitted from the material form of the book, and that engagement and manipulation of this form was not just tolerated, but expected, and perhaps actively encouraged.